Status of Law in International Society - Falk, Richard A. (Book collections on Project MUSE., 1970)
Professor Falk gives special attention to the political setting that shapes international law and to the creation of those intellectual perspectives which would strengthen world order.Originally published in 1970.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.